Preparation method of in-situ A13Ti / Al composite material
Through two-step high-energy ball milling method and powder metallurgy process, high content and small particle size A13Ti was successfully prepared, solving the problem of insufficient performance of A13Ti in the prior art, and achieving high strength and thermal stability of the material.
Patent Information
- Application Number
- CN202411391991.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult to obtain A13Ti with high content and small particle size at the same time in the prior art, resulting in insufficient performance of aluminum-based composite materials.
The MAX-phase ceramic particles were mixed with aluminum powder by using two-step high-energy ball milling method, and fine A13Ti particles were prepared by cold pressing molding, powder metallurgy sintering and plastic deformation processing.
The fine particle size and high content of A13Ti are achieved, the room temperature strength and thermal stability of the material are improved, and the process is simple and the reaction efficiency is high.
Smart Images

Figure CN119410946A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum-based composite materials and particularly relates to an in-situ aluminum-based composite material. 3 Preparation method of Ti / Al composite material. Background Art
[0002] Aluminum-based composite materials have great application prospects in fields that are very sensitive to structural weight, such as rail transportation, aerospace, and military equipment, due to their high specific strength and specific stiffness. 3 Ti has a high melting point (~1623 K), low density (3.4 g / cm 3 ), high Young's modulus (216 GPa) and low high-temperature coarsening rate, making it an ideal reinforcement phase for particle-reinforced aluminum matrix composites.
[0003] In order to obtain the lightweight, high-strength and high-modulus A1 3 Ti / Al composite materials generally require the introduction of a large amount of dispersed Al 3 Ti particles, but it is still difficult to obtain both high content and small particle size A1 3 The problem of Ti. At present, the preparation of A1 3 Ti / Al composite materials are mainly made of powder metallurgy or casting process. 2 AlF 6 A1 was obtained in situ by the reaction of 3 Ti, this method can obtain high content of Al 3 Ti, but its size is usually very coarse and easy to agglomerate. 3 Ti size and promote its dispersion distribution. Some reports use ultrasonic vibration, high shear and other auxiliary casting, or stir friction method for secondary processing, but this increases the process cost and is limited by the stir friction process itself, making it difficult to prepare bulk materials. In addition, some reports use mechanical alloying process to produce Al-TiO 2 、Al-TiH 2 、Al-Al 2 TiO 5 、Al-TiO(OH) 2 In-situ acquisition of fine A1 3 Ti, but affected by the byproduct of the interface reaction - nano-Al 2 O 3 The limitation of high strengthening efficiency makes it impossible to obtain high content of A1 3 Ti / Al composite materials.
[0004] Therefore, how to design a method with simple process, high reaction efficiency and Al 3 Ti small and diffuse A1 3The preparation process and material system of Ti / Al composite materials have become problems to be solved by technicians in this field. Summary of the invention
[0005] The purpose of the present invention is to overcome the existing in situ A1 3 Ti material system and preparation process are difficult to obtain high content and small particle size A1 3 To solve the problem of Ti, an in-situ A1 3 Preparation method of Ti / Al composite material.
[0006] The present invention provides an in situ A1 3 A method for preparing a Ti / Al composite material, the steps of the preparation method are as follows: (1) mixing MAX phase ceramic particles and aluminum powder in a certain ratio, and subjecting the mixed powder to high-energy ball milling to obtain a first raw material powder; (2) mixing the first raw material powder obtained in step (1) and aluminum powder in a certain ratio, and subjecting the mixed powder to high-energy ball milling to obtain a second raw material powder; (3) The second raw material powder obtained in step (2) is subjected to cold pressing, powder metallurgy sintering and plastic deformation processing to obtain A1 3 Ti / Al composite materials.
[0007] In step (1), the aluminum powder is one or more of aluminum powder, aluminum alloy powder, and a mixed powder of aluminum powder and alloy element (Si, Mg, Cu, Zn) powder, and the average particle size is 2-50 μm; the MAX phase ceramic particles are Ti 2 AlC or Ti 3 AlC 2 The average particle size of the MAX phase ceramic particles is 1-100 μm, and the content of the MAX phase ceramic particles in the mixed powder is 80-90 wt.%.
[0008] The ball milling process in step (1) is as follows: the ball-to-material weight ratio is 5:1 to 30:1, the rotation speed is 220-400 rpm, the ball milling time is 2-20 h, and high-energy ball milling is performed under an argon atmosphere. The MAX phase is crushed and a high-energy surface is generated. After ball milling, the average particle size of the MAX phase is less than 1 μm.
[0009] Nano-Al can be added in step (1) 2 O 3 Particles as grinding aids (nano Al 2 O 3 The particle content is 1-3 vol.%, the average particle size is 5-100 nm), which improves the ball milling efficiency, forms high-energy defects and diffusion channels, and achieves hybrid strengthening.
[0010] The aluminum powder in step (2) is one or more of aluminum powder, aluminum alloy powder, and a mixed powder of aluminum powder and alloy element (Si, Mg, Cu, Zn) powder, and has an average particle size of 2-50 μm; the content of the first raw material powder in the mixed powder is 1-25wt.%.
[0011] The ball milling process in step (2) is as follows: the ball-to-material weight ratio is 5:1 to 30:1, the rotation speed is 220-400 rpm, the ball milling time is 2-20 h, and high-energy ball milling is performed under an argon atmosphere to promote uniform distribution of the MAX phase and powder bonding.
[0012] In step (3), the cold pressing forming process is as follows: the second raw material powder obtained in step (2) is loaded into a mold, pre-pressed at 60-120 MPa, and pressed into a green body; the powder metallurgy sintering in step (3) adopts vacuum hot pressing sintering, hot isostatic pressing or spark ion beam sintering process under vacuum conditions, the sintering temperature is 550-650 ° C, the sintering time is 1-3 h, and A1 3 Ti is evenly distributed in the aluminum matrix and has an average particle size of less than 1 μm; the plastic deformation processing in step (3) is performed by forging, rolling and extrusion at 400-630 °C.
[0013] The present invention has the following advantages and beneficial effects: 1. Compared with micron Ti particles, micron MAX phase particles are more easily broken during ball milling. High-energy ball milling can greatly refine the MAX phase and introduce high-energy defects and diffusion channels, thereby promoting the interfacial reaction during the sintering process, which is conducive to obtaining fine Al 3 Ti particles.
[0014] 2. Compared with TiO 2 Nanoparticles such as micron MAX phase can be added in large quantities in the Al matrix, and the reaction efficiency is high during the sintering process, avoiding the problems of easy agglomeration and limited addition amount when using nanophase as raw material.
[0015] 3. Compared with the traditional A1 3 Ti / Al composite material with finer Al 3 Ti size and taller A1 3 Ti content, A1 3 The average Ti particle size is 0.05-0.8 μm, the content is 10-40 vol.%, and the unreacted MAX phase content is less than 2 wt.%. At the same time, A1 3 Ti / Al composite materials have higher room temperature strength and thermal stability. For example, the strength at room temperature can reach over 600 MPa, and the strength at 350°C can reach over 240 MPa.
[0016] 4. Compared with the one-step ball milling method, the two-step ball milling method has the advantages of high particle refinement efficiency and particle dispersion. The first step of the ball milling process mainly ball mills the MAX phase to refine the MAX phase and produce high-energy defects to promote the interface reaction in the subsequent sintering process: during the ball milling process, the high-energy grinding balls collide with the MAX phase particles, and the strong mechanical action causes the MAX phase particles to deform and break, the average particle size is significantly reduced, and the surface energy is greatly increased; a small amount of aluminum powder added during the ball milling process can diffuse into the defects of the MAX phase, providing a rapid diffusion channel for aluminum atoms to enter the MAX phase during the subsequent sintering process, thereby promoting the interface reaction; in addition, nano-Al can be added 2 O 3 The particles act as grinding aids to further improve the ball milling efficiency and achieve hybrid strengthening. The second step of the ball milling process is mainly used to promote the uniform distribution of MAX phase particles and refine the aluminum powder, promote the powder bonding in the subsequent sintering process, and obtain ultrafine grained A1 with uniform organization and performance. 3 Ti / Al composite materials.
[0017] 5. The preparation can be achieved by high-energy ball milling and powder metallurgy. The powder is easy to sinter and has high preparation efficiency, which can realize large-scale engineering preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A1 prepared in Example 1 3 Scanning electron microscope photo of Ti / Al composite material; the dark part is Al matrix and the gray part is Al 3 Ti particles, white part Ti 2 AlC particles; Figure 2 A1 prepared in Example 2 3 SEM photo of room temperature tensile fracture of Ti / Al composite material; Figure 3 A1 prepared in Example 3 3 Scanning electron microscope photograph of the 350℃ tensile fracture of Ti / Al composite material. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0020] Example 1 Weigh 200 g of aluminum powder (average particle size 2 μm), Ti 2 800 g of AlC particles (average particle size 1 μm) were mixed in a stirred high-energy ball mill with a ball-to-material ratio of 5:1 (i.e., grinding ball: (aluminum powder 200 g + Ti 2AlC particles 800 g) = 5:1), the speed was 220 rpm, and the ball milling time was 20 h to obtain the first raw material powder. Then, spherical aluminum powder with an average particle size of 2 μm was selected, 750 g of aluminum powder and 250 g of the first raw material powder were weighed, and mixed using a stirring high-energy ball mill with a ball-to-material ratio of 15:1 (i.e., grinding ball: (aluminum powder 750 g + first raw material powder 250 g) = 15:1), the speed was 220 rpm, and the ball milling time was 7 h to obtain the second raw material powder. The second raw material powder was vacuum hot-pressed and sintered at 550 ℃ and 200 MPa for 2 hours, and the sintered ingot was hot-extruded at 500 ℃ with an extrusion ratio of 7:1 to obtain the final material.
[0021] A1 prepared in this example 3 Ti / Al composite materials, of which A1 3 The Ti particle size is about 0.3 μm, and the unreacted Ti 2 The AlC content is less than 2 wt.%, and the composite material has a uniform structure. Its microstructure morphology is as follows Figure 1 As shown, the dark part is the Al matrix and the gray part is the A1 3 Ti particles, white part Ti 2 AlC particles.
[0022] Example 2 Weigh 150 g aluminum powder (average particle size 13 μm), Ti 2 850 g of AlC particles (average particle size 25 μm) were mixed in a stirred high-energy ball mill with a ball-to-material ratio of 10:1 (i.e., grinding balls: (aluminum powder 150 g + Ti 2 AlC particles 850 g) = 10:1), the speed was 300 rpm, and the ball milling time was 15 h to obtain the first raw material powder. Then, spherical aluminum powder with an average particle size of 13 μm was selected, 800 g of aluminum powder and 200 g of the first raw material powder were weighed, and mixed using a stirring high-energy ball mill with a ball-to-material ratio of 15:1 (i.e., grinding ball: (aluminum powder 800 g + first raw material powder 200 g) = 15:1), the speed was 400 rpm, and the ball milling time was 6 h to obtain the second raw material powder. The second raw material powder was vacuum hot-pressed and sintered at 650 ° C and 100 MPa for 2 hours, and the sintered ingot was hot-extruded at 550 ° C with an extrusion ratio of 7:1 to obtain the final material.
[0023] A1 prepared in this example 3 Ti / Al composite materials, of which A1 3 The Ti particle size is about 0.5 μm, and the unreacted Ti 2 The AlC content is less than 2 wt.%, and the composite material has uniform structure and good performance. The room temperature tensile fracture morphology is as follows Figure 2 As shown, A13 Ti particles are distributed at the bottom of the dimple.
[0024] Example 3 Weigh 100 g of aluminum powder (average particle size 25 μm), Ti 3 AlC 2 900 g of particles (average particle size 50 μm) were mixed using a stirred high-energy ball mill with a ball-to-material ratio of 15:1 (i.e., grinding balls: (aluminum powder 100 g + Ti 3 AlC 2 The first raw material powder was obtained by mixing 900 g of aluminum powder and 100 g of the first raw material powder with a speed of 400 rpm and a ball milling time of 6 h. Then, a spherical aluminum powder with an average particle size of 25 μm was selected, and 900 g of aluminum powder and 100 g of the first raw material powder were weighed and mixed using a stirring high-energy ball mill. The ball-to-material ratio was 15:1 (i.e., grinding ball: (aluminum powder 900 g + first raw material powder 100 g) = 15:1), the speed was 220 rpm, and the ball milling time was 7 h to obtain the second raw material powder. The second raw material powder was vacuum hot-pressed and sintered at 650 ° C and 100 MPa for 2 hours, and the sintered ingot was hot-extruded at 500 ° C with an extrusion ratio of 7:1 to obtain the final material.
[0025] A1 prepared in this example 3 Ti / Al composite materials, of which A1 3 The Ti particle size is about 0.5 μm, and the unreacted Ti 3 AlC 2 The content is less than 2 wt.%, and the composite material has uniform structure and good performance. Its high temperature (350 ℃) tensile fracture morphology is as follows Figure 3 As shown, A1 3 Ti particles are distributed at the bottom of the dimple.
[0026] Example 4 Weigh 195 g aluminum powder (average particle size 50 μm), Ti 2 AlC particles 800 g (average particle size 100 μm), Al 2 O 3 5 g of particles (average particle size 10 nm) were mixed using a stirred high-energy ball mill with a ball-to-material ratio of 30:1 (i.e., grinding balls: (aluminum powder 195 g + Ti 2 AlC particles 800 g + Al 2 O 3The first raw material powder was obtained by mixing 950 g of aluminum powder and 50 g of the first raw material powder with a speed of 400 rpm and a ball milling time of 2 h. Then, a spherical aluminum powder with an average particle size of 50 μm was selected, and 950 g of aluminum powder and 50 g of the first raw material powder were weighed and mixed using a stirring high-energy ball mill. The ball-to-material ratio was 15:1 (i.e., grinding ball: (950 g of aluminum powder + 50 g of the first raw material powder) = 15:1), the speed was 400 rpm, and the ball milling time was 6 h to obtain the second raw material powder. The second raw material powder was vacuum hot-pressed and sintered at 610 ° C and 100 MPa for 2 hours, and the sintered ingot was hot-extruded at 450 ° C with an extrusion ratio of 7:1 to obtain the final material.
[0027] This example prepares A1 3 Ti-Al 2 O 3 / Al composite materials, of which A1 3 The Ti particle size is about 0.5 μm, and the unreacted Ti 2 The AlC content is less than 2 wt.%, the composite material has uniform structure, and the added nano-Al 2 O 3 and in situ generated submicron A1 3 Ti produces mixed strengthening, and the strength is better than that without adding Al 2 O 3 A1 prepared by ball milling 3 Ti / Al composite materials are high.
[0028] Comparative Example 1 Weigh 200 g of aluminum powder (average particle size 25 μm), Ti 3 AlC 2 800 g of particles (average particle size 50 μm) were mixed using a stirred high-energy ball mill with a ball-to-material ratio of 15:1 (i.e., grinding balls: (aluminum powder 200 g + Ti 3 AlC 2 The first raw material powder was obtained by mixing 800 g of aluminum powder and 200 g of the first raw material powder with a speed of 400 rpm and a ball milling time of 6 h. Then, a spherical aluminum powder with an average particle size of 25 μm was selected, and 800 g of aluminum powder and 200 g of the first raw material powder were weighed and mixed using a stirring high-energy ball mill. The ball-to-material ratio was 15:1 (i.e., grinding ball: (aluminum powder 800 g + first raw material powder 200 g) = 15:1), the speed was 400 rpm, and the ball milling time was 6 h to obtain the second raw material powder. The second raw material powder was vacuum hot-pressed and sintered at 500 °C and 200 MPa for 2 hours, and the sintered ingot was hot-extruded at 450 °C with an extrusion ratio of 7:1 to obtain the final material.
[0029] The material of Comparative Example 1 prepared was unable to obtain a dense material due to the low sintering temperature, and a large amount of unreacted Ti 3 AlC 2 Particles.
[0030] Comparative Example 2 Weigh 200 g of aluminum powder (average particle size 50 μm), Ti 2 800 g of AlC particles (average particle size 30 μm) were mixed using a planetary ball mill with a ball-to-material ratio of 3:1 (i.e., grinding ball: (aluminum powder 200 g + Ti 2 AlC particles 800 g) = 3:1), the speed was 100 rpm, and the ball milling time was 6 h to obtain the first raw material powder. Then, spherical aluminum powder with an average particle size of 50 μm was selected, 850 g of aluminum powder and 150 g of the first raw material powder were weighed, and a planetary ball mill was used for mixing. The ball-to-material ratio was 3:1 (i.e., grinding ball: (aluminum powder 850 g + first raw material powder 150 g) = 3:1), the speed was 100 rpm, and the ball milling time was 6 h to obtain the second raw material powder. The second raw material powder was vacuum hot pressed and sintered at 650 ° C and 100 MPa for 2 hours, and the sintered ingot was hot extruded at 500 ° C with an extrusion ratio of 7:1 to obtain the final material.
[0031] The Ti prepared in Comparative Example 2 2 AlC-A1 3 Ti / Al composite materials, due to the low ball milling energy, Ti 2 AlC particles agglomerate, A1 3 Ti is coarse and there is a lot of unreacted Ti in the aluminum matrix 2 AlC particles.
[0032] Comparative Example 3 Weigh 800 g of aluminum powder (average particle size 5 μm), Ti 2 200 g of AlC particles (average particle size 10 μm) were mixed in a stirred high-energy ball mill with a ball-to-material ratio of 15:1 (i.e., grinding balls: (aluminum powder 800 g + Ti 2 AlC particles 200 g) = 15:1), rotation speed 400 rpm, ball milling time 6 h. Then the mixed powder was sintered at 610 ° C, 100 MPa under vacuum hot pressing for 2 hours, and the sintered ingot was hot extruded at 500 ° C with an extrusion ratio of 7:1 to obtain the final material.
[0033] A1 prepared in Comparative Example 3 3 Ti / Al composite materials contain a lot of unreacted Ti 2 AlC particles. 2The AlC particles were not refined enough, even though the TiO2 2 The average particle size of AlC particles is larger than that of Ti obtained by two-step ball milling. 2 The average particle size of AlC particles. 2 The number of high-energy defects and atomic diffusion channels generated by AlC during the ball milling process decreased, resulting in the Al1 3 Under the same powder metallurgy sintering process, the nucleation rate of Ti is reduced. 3 There will be a lot of unreacted Ti in the Ti / Al composite material. 2 AlC particles.
[0034] Comparative Example 4 Spherical aluminum powder with an average particle size of 13 μm was selected and ball-milled into flakes using a stirring high-energy ball mill with a ball-to-material ratio of 10:1 (i.e., grinding ball: aluminum powder = 10:1), a rotation speed of 300 rpm, and a ball milling time of 10 h. 3 AlC 2 The particles were prepared by a stirred high-energy ball mill with a ball-to-material ratio of 10:1 (i.e., grinding ball: Ti 3 AlC 2 The powder was milled at a speed of 300 rpm for 12 h until it was in flake form. 800 g of flake aluminum powder and 800 g of flake Ti were weighed. 3 AlC 2 200 g of particles were mixed in a stirred high-energy ball mill with a ball-to-material ratio of 3:1 (i.e., grinding balls: (800 g of flaky aluminum powder + 800 g of flaky Ti 3 AlC 2 The mixed powder was sintered at 610 °C and 100 MPa for 2 hours under vacuum hot pressing, and the sintered ingot was hot extruded at 500 °C with an extrusion ratio of 7:1 to obtain the final material.
[0035] The Ti prepared in Comparative Example 4 3 AlC 2 -A1 3 Ti / Al composite materials contain a lot of unreacted Ti 3 AlC 2 Particles, and A1 3 Ti is coarse in size. 3 AlC 2 The particles are ball milled separately to make Ti 3 AlC 2 The particle size is significantly reduced, but due to the lack of aluminum powder, Ti 3 AlC 2The high-energy defects generated were not filled and no effective diffusion channels could be formed, resulting in A1 3 The nucleation rate of Ti is reduced.
[0036] Although the present invention has been disclosed as above in some embodiments, it is not intended to limit the present invention. Any technical personnel in this field can make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the main purpose and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an in-situ Al3Ti / Al composite material, characterized in that: The preparation method steps are as follows: (1) mixing MAX phase ceramic particles and aluminum powder in a certain ratio, and subjecting the mixed powder to high-energy ball milling to obtain a first raw material powder; (2) mixing the first raw material powder obtained in step (1) and aluminum powder in a certain ratio, and subjecting the mixed powder to high-energy ball milling to obtain a second raw material powder; (3) The second raw material powder obtained in step (2) is subjected to cold pressing, powder metallurgy sintering and plastic deformation processing to obtain an A13Ti / Al composite material.
2. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: In the step (1), the aluminum powder is one or more of aluminum powder, aluminum alloy powder, and a mixed powder of aluminum powder and alloy element (Si, Mg, Cu, Zn) powder, and has an average particle size of 2-50 μm; the MAX phase ceramic particles are Ti2AlC or Ti3AlC2, and the average particle size of the MAX phase ceramic particles is 1-100 μm, and the content of MAX phase ceramic particles in the mixed powder is 80-90 wt.%.
3. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: The ball milling process in step (1) is as follows: the ball-to-material weight ratio is 5:1 to 30:1, the rotation speed is 220-400 rpm, the ball milling time is 2-20 h, and high-energy ball milling is performed under an argon atmosphere, the MAX phase is crushed and a high-energy surface is generated, and the average particle size of the MAX phase after ball milling is less than 1 μm.
4. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: In the step (1), nano-Al2O3 particles can be added as a grinding aid to improve the ball milling efficiency, form high-energy defects and diffusion channels, and achieve hybrid strengthening.
5. The method for preparing the in-situ Al3Ti / Al composite material according to claim 4, characterized in that: The content of nano-Al2O3 particles in the first raw material powder is 1-3 vol.%, and the average particle size is 5-100 nm.
6. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: The aluminum powder in step (2) is one or more of aluminum powder, aluminum alloy powder, and a mixed powder of aluminum powder and alloy element (Si, Mg, Cu, Zn) powder, and has an average particle size of 2-50 μm; the content of the first raw material powder in the mixed powder is 1-25 wt.%.
7. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: The ball milling process in step (2) is as follows: the ball-to-material weight ratio is 5:1 to 30:1, the rotation speed is 220-400 rpm, the ball milling time is 2-20 h, and high-energy ball milling is performed under an argon atmosphere.
8. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: The cold pressing process in step (3) is as follows: the second raw material powder obtained in step (2) is loaded into a mold, pre-pressed at 60-120 MPa, and pressed into a green body.
9. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: The powder metallurgy sintering in the step (3) adopts vacuum hot pressing sintering, hot isostatic pressing or discharge ion beam sintering process under vacuum conditions, the sintering temperature is 550-650°C, the sintering time is 1-3 h, and the A13Ti is evenly distributed in the aluminum matrix and the average particle size is less than 1 μm.
10. The method for preparing the in-situ Al3Ti / Al composite material according to claim 1, characterized in that: The plastic deformation processing in the step (3) is performed by forging, rolling and extrusion at 400-630°C.